Analisis Story Drift dan Kondisi Sendi Plastis Berbasis Performa pada Gedung Bertingkat dengan Konfigurasi Struktur Persegi Panjang, U, L, H, dan T - Rahmantyo, Aji; Andayani, Relly (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
Strength based design is commonly used in the design of resisting earthquake building. It is analyzed by linear elastic method so that it can’t describe the seismic behaviour of the structures. For that reason, the design of structure needs to consider performance based design. Irregularity of structure play important role for the results of Structure Performance. This paper uses five models of 20 storey reinforced concrete building with same height(76 m) and areas(750m2) with different plan configurations: rectangular, T, L, U, and H-shaped. Non linear time history method is used  to investigate the seismic behaviour of the structures, using finite model with ETABS2016. Dimension of structures are column (600 x1000 mm), shear wall (400mm), couple-beam (400x900 mm), slab (140mm). Recorded accelorogram used in this paper are Altadena, Array, Corralit, LACC, and Yermo because it has almost same earthquake mechanism, magnitude, and epicentrum distance, so that they are used as an artificial accelorogram that is synthesized using Wavelet Function according to SNI 1726-2012.Result shows that the story drift and plastic hinges for collapse prevention (CP) are: rectangular (story drift is 0.59% and amount of CP hinges are 8), H-shaped (1.58%/23), L-shaped (2.41%/30), U-shaped (4.59%/35), T-shaped (5.8%/58).